Active Learning and its Impact on Higher-Order Thinking Skills in Preschool Science Education (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Active learning strategies engage preschool children to use higher order thinking skills such as critical thinking and problem solving, however this method of teaching is underused in favor of traditional methods.  A background and literature review will establish the effectiveness of using active learning strategies with early learners in science instruction.  This article will address reasons teachers do not implement higher order learning strategies in the classroom and attempt to refute these reasons.  This article establishes that a teacher does not need to have “mastered” this strategy in order to implement it.  Suggestions and examples will be given for how to transform a standard preschool lesson into one that engages higher order thinking skills through the use of active learning strategies.